Throwback to pre-pandemic days: A photo-elicitation study on organizational nostalgia - Tatar, Berivan; Muceldili, Busra; Erdil, Oya (Sage Publications Inc, 2023)
BACKGROUND: As an unprecedented outbreak, the COVID-19 pandemic has restricted and dramatically changed several respects of life. In terms ofworking life, the transition to a remoteworking system has brought several changes and interrupted the continuity between past and present working life. In this case, this adversity has led people to past experiences and memories, and many people have used nostalgia as a crucial resource for alleviating the negative impact of the outbreak. OBJECTIVE: In this context, as a form of nostalgia, the current study particularly investigated memories eliciting organizational nostalgia and antecedents and consequences of organizational nostalgia in the pandemic era. METHODS: Photo-elicitation interview in general, and participant-driven photo-elicitation in particular, was used as a data collection method. A cross-sectional design was employed for this study. In total, 10 photo-elicitation interviews through 62 photos were carried out with participants in Turkey. The thematic analysis was used for coding and analyzing the interviews. RESULTS: The current study demonstrated that (1) participants feel nostalgic for managers, colleagues, events, job, and working environment-related memories; (2) lack of social connectedness, loneliness, anxiety, fear, and uncertainty triggers pandemic-induced nostalgia; and (3) pandemic-induced organizational nostalgia has an impact on the variety of emotions (regret, hope, pride, freedom, joy, peace, excitement, yearning, gratitude, sadness, and happiness) of employees in the pandemic era. CONCLUSIONS: This study contributes to overcoming the lack of studies investigating the nostalgic emotion of employees in the pandemic era and how this emotion might contribute to overcoming the effects of COVID-19.
Keywords: Nostalgia; organizational nostalgia; photo-elicitation; qualitative research; COVID-19